The EU and the global financial crisis: new varieties of capitalism - Schweiger, Christian (Cheltenham, 2014)
"The EU And The Global Financial Crisis analyses the emerging new political economy of the EU Single Market in the wake of the 2008–2009 global financial crisis. The crisis has initiated a new wave of functionalist spillover towards deeper integration in the eurozone, which in effect divides the EU into multiple integrative cores. Providing the first comprehensive examination of the emerging policy framework in the EU and the eurozone after the global financial crisis, this rigorous study applies a neofunctionalist approach to the analysis of the crisis implications by considering the emergence of the system of multiple cores in the EU as a result of the return of political spillover. It outlines the EU’s post-crisis varieties of capitalism and examines the effects of the financial crisis on selected key economies in the Single Market This authoritative book offers a complete breakdown of the EU’s political economy in the wake of the global financial crisis and will therefore appeal to students of European politics, international political economy and European studies, as well as policy-makers and other stakeholders."